Aplikasi Berbasis Android untuk Pembelajaran: Potensi dan Metode Pengembangan (Jurusan Matematika FMIPA UNNES, 2018)
Almost half of adults (43%) in Indonesia have smartphones. Smartphone market share in Indonesia around 83.99% dominated by the Android operating system. Google specially designs the Android operating system -that uses the Linux kernel base- for a touch-screened smartphone. The massive use of Android-based phones has led many researchers to develop mobile learning (m-learning), Android-based learning media, Android-assisted learning model, and Android app for classroom management. This article will discuss how the potential use of Android in mathematics learning and methods we can use in developing Android applications.